2019
DOI: 10.1002/jcb.29545
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic microRNA‐765 promotes the growth and metastasis of breast carcinoma by directly targeting ING4

Abstract: Previous investigations have proved that microRNA (miR)‐765 is significantly overexpressed in multiple tumor types. Nevertheless, the underlying molecular mechanism of miR‐765 in mediating breast carcinoma cell growth and metastasis remains unclear. Quantitative real‐time polymerase chain reaction was used to determine the levels of miR‐765 and inhibitor of growth 4 (ING4) in breast carcinoma tissues and breast carcinoma cells. Cell proliferation, colony formation, wound healing, and Transwell invasion assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…21,22 Besides, miR-765 plays oncogenic or anti-cancer roles in gastric cancer and breast cancer. 23,24 Its role in glioma remains unclear. Our results suggested that miR-765 was a tumor suppressor in glioma.…”
Section: Dovepressmentioning
confidence: 99%
“…21,22 Besides, miR-765 plays oncogenic or anti-cancer roles in gastric cancer and breast cancer. 23,24 Its role in glioma remains unclear. Our results suggested that miR-765 was a tumor suppressor in glioma.…”
Section: Dovepressmentioning
confidence: 99%
“…14 It also has been reported that miR-765 was dysregulated and participated in the progression of many other cancers, including esophageal squamous cell carcinoma, breast cancer, prostate cancer, and renal cell carcinoma, etc. [15][16][17][18] In the previously reported miRNA expression file in NSCLC, miR-765 was found to be upregulated but its role in the progression of NSCLC was unclear. This study focused on the role of miR-765 in the prognosis and progression of NSCLC by qRT-PCR, CCK8, and Transwell assay aimed to provide a novel insight into the therapy and management of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…miR-466 declined the growth and metastasis of prostate cancer by directly targeting the bone-associated transcription factor RUNX2 [41] . miR-765 regulated the growth and metastasis of breast cancer by regulating the Mir-765-ING4 negative feedback loop [42] . These literature studies suggested that miRNA markers associated with cuproptosis may be associated with the progression of TC and BC, and reveal expected targets for the treatment of TC and BC.…”
Section: Discussionmentioning
confidence: 99%